Loss of contralateral upper limb motor evoked potential due to occlusion of the internal carotid artery in microsurgical clipping of basilar tip aneurysm - Seng, Liew; Yasuhiro, Yamada; Rajagopal, Niranjana; Mohammad, Ameen; Takao, Teranishi; Kyosuke, Miyatani; Tsukasa, Kawase; Kato, Yoko (Asian Journal of Neurosurgery, 2019)
The motor evoked potential (MEP) monitoring is routinely used as an adjunct in the microsurgical clipping of anterior circulation. We describe a case of unruptured basilar tip aneurysm treated with microsurgical clipping developed loss in MEP recording of the left abductor pollicis brevis (APB) following clipping of basilar tip aneurysm. A 58-year-old man was referred to the Fujita Health University Banbuntane-Hotokukai Hospital, Nagoya, Aichi, Japan, with incidental finding of unruptured 6.5 mm basilar tip saccular aneurysm. He underwent right anterior temporal approach of basilar tip aneurysm clipping. The internal carotid artery (ICA) was mobilized laterally to allow direct visualization of the neck of the basilar tip aneurysm. Following the application of temporary clip and subsequently permanent clip at the neck of the aneurysm, the MEP signal was lost in the left APB. The temporary clip was immediately removed. Dual-image videoangiography (DIVA) showed a filling defect in the right ICA and a branch of middle cerebral artery (MCA). The MEP was absent for about 23 minutes and the amplitude improved to only 75% of the baseline recording at 38 minutes till the end of the surgery. A repeat DIVA showed good flow within the right ICA and MCA. Glasgow coma score was 15/15 on postoperative day 1 and there was no gross motor or sensory deficit except right oculomotor nerve palsy with complete recovery at 6 months follow-up. This is the first reported ICA occlusion due to its mobilization in microsurgical clipping of basilar tip aneurysm. The use of neuromonitoring especially MEP is essential even in the posterior circulation aneurysm surgery especially when excessive manipulation of the ICA is unavoidable. When performing intraoperative angiography for aneurysm surgery, it is prudent to detect any filling defect within the surrounding vessels.
Keywords: Basilar tip aneurysm; internal carotid artery; motor evoked potential; posterior circulation